Downward migration and transfer to plants of radiocaesium in Scottish soil profiles : a comparison with earlier studies - Thored, Kristin (SLU/Dept. of Soil and Environment, 2010)
Following the accident at the nuclear power plant in Chernobyl in 1986, great volumes of 137Cs were distributed over large parts of the former Soviet Union and Europe. Over Scotland, radiocaesium was deposited as wet deposition. Due to the relatively long physical half-life of 30 years, there are still measurable activity concentrations in the natural environment. This study was made on two organic soils, Knockandy Hill and Rora Moss, situated in the eastern part of the central highlands of Scotland. At these two sites, studies on migration and transfer between soil and plants were conducted. The aim of the thesis was to present the current state of radiocaesium in the Scottish soils and to compare these data with data from earlier studies, however, it was difficult to make any implications from this study due to variations in sampling techniques. Another aim was to study the transfer of 137Cs from soil to plant. Caesium resembles potassium and is readily fixed to clay minerals in the soil and weakly bound to organic matter. Plants have a difficulty in discriminating between the two elements, hence the uptake of caesium can be considerable. This study has, in accordance with other similar studies, shown that the transfer of radiocaesium to heather (Calluna vulgaris) is significantly higher than the transfer to different grass species. Concerning the movement of caesium in the soils no significant difference could be found between the two organic soils. Their migration depths were 8.2 and 8.8 cm and their migration rates were 0.36 and 0.39 cm y-1 for Knockandy Hill and Rora Moss, respectively.